The role of anatomic ACL reconstruction in ACL revision surgery - Tisherman, Robert; De Groot, Joseph; Rothrauff, Benjamin; Byrne, Kevin; Meredith, Sean J.; Musahl, Volker (Annals of Joint; Vol 3 (December 2018): Annals of Joint, 2018)
Revision anterior cruciate ligament (ACL) reconstruction is a technically demanding procedure with more challenges than primary ACL reconstruction. The etiology of primary ACL reconstruction failure is most commonly due to technical error. Determining the cause of ACL failure is the primary objective, and careful preoperative planning is of the utmost importance. It is imperative to incorporate anatomic revision ACL reconstruction principles to restore rotatory stability. This article reviews anatomic revision ACL reconstruction, including preoperative evaluation, surgical technique, pitfalls, and outcomes.